Advances in Soft Computing 10th Mexican International Conference on Artificial Intelligence, MICAI 2011, Puebla, Mexico, November 26 - December 4, 2011, Proceedings, Part II - Batyrshin, Ildar; Sidorov, Grigori; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The two-volume set LNAI 7094 and 7095 constitutes the refereed proceedings of the 10th Mexican International Conference on Artificial Intelligence, MICAI 2011, held in Puebla, Mexico, in November/December 2011. The 96 revised papers presented were carefully selected from XXX submissions. The second volume contains 46 papers focusing on soft computing. The papers are organized in the following topical sections: fuzzy logic, uncertainty and probabilistic reasoning; evolutionary algorithms and other naturally-inspired algorithms; data mining; neural networks and hybrid intelligent systems; and computer vision and image processing.
Keywords: Computer science; Data mining; Artificial intelligence; Computer vision; Optical pattern recognition; Computer Science; Artificial Intelligence (incl. Robotics).; Computer Imaging, Vision, Pattern Recognition and Graphics; Image Processing and Computer Vision; Information Systems Applications (incl. Internet).; Pattern Recognition; Data Mining and Knowledge Discovery